LINGUISTIC, CULTURAL, AND EDUCATIONAL RIGHTS OF MINORITIES MEDIATING INTER-ETHNIC RECONCILIATION AND PROMOTING INCLUSIVENESS: THE CASE OF KOSOVO - Avdi SMAJLJAJ (Eastern European Journal of Regional Studies)
Multiethnicity is one of the fundamental conditions of Kosovo's statehood. It constituted the backbone of Ahtisaari’s final status settlement proposal, internalized within the constitution and institutional structure. Linguistic, cultural, educational, and political rights are granted by the constitution and laws referring to minorities. However, despite the legal and institutional foundations of minority rights, on the terrain, there seem to be still challenges in implementing and enjoying those rights by minorities. Thus, the paper aims to look at the extent to which linguistic, cultural, and educational rights are being implemented and enjoyed by minorities, from their establishment up to the present, through exploring a number of research questions. What are the challenges and obstacles to the implementation of those rights? How these challenges are reflected in inclusiveness and interethnic reconciliation? The paper is based on legal documents, statistical data, reports, and studies on minority rights in Kosovo.